2019
DOI: 10.32763/juke.v12i2.170
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Berhubungan Dengan Kejadian Penyakit Scabies Pada Santri

Abstract: Scabies adalah penyakit kulit yang disebabkan infestasi dan sensitisasi tungau Sarcoptes scabiei. Penyakit scabies umumnya menyerang individu yang hidup berkelompok seperti asrama dan pesantren. Prevalensi scabies di Pondok Pesantren Darul Ma'arif Kabupaten Sintang sebanyak 24 orang, mengalami peningkatan dari tahun ketahun menjadi 43 orang. Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor yang berhubungan dengan kejadian scabies. Jenis penelitian adalah observasional dengan pendekatan analitik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Some male students who did not perceive that not getting treatment could worsen their condition, meaning that there were respondents who felt susceptible but did not seek treatment. These results are in accordance with previous research conducted by Samosir & Sunarti (2019) which showed that there were more respondents with poor treatment-seeking behavior (54.40%) compared to respondents with good treatment-seeking behavior (45.60%). An OR value of 3.19 was obtained, which means that respondents with poor treatment-seeking behavior had a risk of getting scabies 3.19 times greater than those with good treatment-seeking behavior.…”
Section: Relationship Between Perceptions Of Individual Susceptibility and Actions Of Taking Treatmentsupporting
confidence: 93%
See 1 more Smart Citation
“…Some male students who did not perceive that not getting treatment could worsen their condition, meaning that there were respondents who felt susceptible but did not seek treatment. These results are in accordance with previous research conducted by Samosir & Sunarti (2019) which showed that there were more respondents with poor treatment-seeking behavior (54.40%) compared to respondents with good treatment-seeking behavior (45.60%). An OR value of 3.19 was obtained, which means that respondents with poor treatment-seeking behavior had a risk of getting scabies 3.19 times greater than those with good treatment-seeking behavior.…”
Section: Relationship Between Perceptions Of Individual Susceptibility and Actions Of Taking Treatmentsupporting
confidence: 93%
“…Respondents who did not seek treatment failed to do so because they did not feel susceptible. This means that the more the respondent feels susceptible, the greater their concern for disease, meaning that the respondent looks for ways to prevent disease from appearing (Samosir & Sunarti, 2019).…”
Section: Relationship Between Perceptions Of Individual Susceptibility and Actions Of Taking Treatmentmentioning
confidence: 99%